Étnias educativas y su incidencia en el aprendizaje significativo de los estudiantes de octavo y noveno año de educación básica de la Unidad Educativa “Tres de Julio”, cantón el carmen, periodo lectivo 2015-2016. - Vélez Torres, Darwin Vicente (2015)
The educational unit 'July 3' is located in the "El Carmen" canton Manabi province, is one of the emblematic institutions of this city, and its mission is provide an active and participatory education with values and principles in accordance with the good living; to achieve the development of skills and the formation of the students. It is an institution with 40 years of experience and that has been a bulwark in the formation of children and youth in this part of the Patria.En today with the new Constitution and new laws, education has many changes, the most important being the decentralization or transfer of responsibilities and resources from the central Government to provincial governments municipal and parochial and above all to the same institutions. Administrative decentralization, i.e. the competencies and attributions of the national level toward distributed levels in zonal 9 coordination; District 140-district and circuit 1117 educational circuits. This new form of organization allows administrative levels of planning, coordination, management and Control, as well as promote universal access to education of quality and warmth through efficiency and effectiveness. In this way it ensures equity, better management and optimization of resources in the territory, under the concept of a planned, decentralized, coordinated and equitable state that offers greater coverage of quality of public services. Faced with this new reality, education and comprehensive training are the cornerstones of the progress of society and for this reason it is essential the study and analysis of the processes handled by the educational institution. The methodology that is applied to collect information, relies on the use of techniques such as: surveys, obtaining in this latter information directly provided by the students, teachers and parents. Through information and collection of data from managers, teachers and students, the following results were obtained: 25% of students feel that apply the process of teaching - learning in the classroom in a direct way, a 12.5% as formal while a 62.5% should be explanatory. Than 50% students indicated that they know are the ethnic groups. Than 25% students indicate that in hour of classes always teacher asked about prior knowledge, 12.5% almost always, while 62.5 percent indicated that sometimes. Than 25% students indicate that your teacher talks about the ethnic group and its jurisdiction, 12.5% almost always, while 62.5% sometimes. That 40% of managers consider that processes within the Unidad Educativa "Tres de Julio", in relation to the teaching process and educational ethnicity are made, 60% expressed that these processes are not carried out. 100% indicate that not are they trained teachers permanently on issues related to the process of teaching - learning and educational groups. 20% of teachers consider that they made permanent evaluations within the institution to assess the level of teaching and learning that teachers bring their students, 80% expressed that evaluations are not conducted. The 100% indicate that they planned not daily classes and values and techniques of teaching and learning as well as educational ethnic groups are found in them. For these aspects of the problem you can define the aspects most relevant. There are flaws in the teaching process. There is a lack of knowledge about existing ethnic groups. That is not made a diagnosis to students to measure their previous knowledge.